The Mauritanian labor market through the lens of the 2004 national household survey - Rajadel, Tania; Pontara, Nicola; Sanchez Puerta, Maria Laura (2012)
This paper provides a snapshot of Mauritania s labor market using data from the 2004 national household survey. The results show that the labor market is characterized by lower participation rates, lower employment-to-population rates, and relatively higher unemployment rates than in neighboring countries. The non poor fare better in the labor market than the poor. Although the labor force participation of the poor is higher than that of the non poor, the poor display a higher unemployment rate and a lower employment rate than the non poor. The data also suggest a negative correlation between wage employment and poverty. Substantial differences in labor market indicators emerge when disaggregating the analysis by gender and age-group. Female non-participation is extremely high. Women systematically earn less than men independently of their sector and type of employment and controlling for other factors, such as education. Young adults face considerable difficulties in entering the labor market: more than half of the population aged 15-24 is neither studying nor participating in the labor force. As gender disparities remain important for similar levels of education, more work is needed to understand whether cultural factors may prevent women from entering the labor market. Concerning young adults, future poverty reduction strategies need to pay more explicit attention to the promotion of employment through informed labor market policies.